Family Ownership Structure, Independent Directors, and Independent Commissioners: Effects on Leverage - Yolanda, Yoke; Utama, Cynthia Afriani (Jurnal Manajemen Bisnis, 2021)
Research aims: The purpose of this research was to examine the direct relationship between family ownership structure and leverage as well as the indirect impact of independent commissioners and independent directors on the relationship between family ownership structure and leverage.Design/Methodology/Approach: This research applied a purposive sampling technique that resulted in 22 Indonesian manufacturing public firms operating from 2010 to 2018 as the research sample. The panel data were collected from Thomson Reuters, and family ownership data were manually collected from company annual reports. This research employed multiple regression analysis with four models.Research findings: The results indicated that family ownership structure was negatively significant to leverage. The independent director was not proven to strengthen the relationship between family ownership structure and leverage but rather was partially proven to do so yet the independent commissioner could not strengthen the relationship between family ownership structure and leverage.Theoretical contribution/ Originality: This research was contributed to develop the relationship between ownership structure in family companies by involving independent commissioners and independent directors.Practitioner/Policy implication: This research’s result can help companies make financing decisions and mitigate agency problems.Research limitation/Implication: The limitations of this research were the sample only focused on manufacturing public firms and Indonesia Stock Exchange has implemented regulations to eliminate the rule requiring each company to have an independent director, which became effective as of December 28, 2018.